2018
DOI: 10.2478/gse-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Assessment of Subsurface Conditions at Proposed Building Sites: Implications for Foundation Failure and Building Collapse

Abstract: Building collapse has been a recurrent environmental hazard in Nigeria in the last two decades. This is a corollary of inadequate foundation investigation prior to construction, poor government policies, and general lack of awareness on the importance of geophysical and geotechnical investigations. In this study, geological mapping and detailed geophysical investigation using Electrical Resistivity Imaging (ERI) and Vertical Electrical Sounding (VES) were carried out to understand the suitability of proposed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…According to the work, spurious features from the 3D effects is often contained is in the image of 2D resistivity survey. Ariyo et al 2018 used electrical resistivity imaging to understand the suitability of a proposed site with Olabisi Onabanjo University campus for building construction. It was concluded that some of the proposed sites were structurally incompetent for engineering or foundation purposes and suggested that excavation of the topsoil is required to sustain the proposed structure.…”
Section: Introductionmentioning
confidence: 99%
“…According to the work, spurious features from the 3D effects is often contained is in the image of 2D resistivity survey. Ariyo et al 2018 used electrical resistivity imaging to understand the suitability of a proposed site with Olabisi Onabanjo University campus for building construction. It was concluded that some of the proposed sites were structurally incompetent for engineering or foundation purposes and suggested that excavation of the topsoil is required to sustain the proposed structure.…”
Section: Introductionmentioning
confidence: 99%